DIRECTIONS OF DEVELOPMENT OF EVALUATION ACTIVITY AND ITS LEGAL BASIS - Bobirjon Aktamov Mardon ugli, (International Journal of Innovations in Engineering Research and Technology, 2023)
The article studied the tariffs given by economists to the concept of regulation of valuation activities. The necessity of regulation of valuation activities and the reasons for adapting the national standards of Yanoga valuation in the Republic of Uzbekistan to world practice are analyzed. The means of state regulation of valuation activities in Uzbekistan are analyzed in detail, directions for the further development of systems for regulating valuation activities are considered.